DRINKING WATER AND SCHOOL HEALTH PROMOTION: ASSESSMENT OF WATER POTABILITY IN TWO PUBLIC SCHOOLS IN EUNÁPOLIS-BA - Almeida da Silva, Flaelma; Lucas Silva D’Araújo , Pedro; Moronari Sandoval , Victor; Torquato Viana Teles, Joel; Sabino da Silva Alves, Marcos; Adrenallina Torres Carvalho, Meure; Serrano Barreiro Bertoldi, Paula; de Paula Andrade da Cunha, Victor; Barbosa Ramos Bandeira Sena, Jéssica; Costa, Marcelo; de Lima, Diana (Health and Society, 2025)
Access to drinking water is a fundamental human right and a key social determinant of health, particularly in the school environment, where the consumption of contaminated water can compromise academic performance and collective well-being. This study assessed the potability of water in two public schools located in Eunápolis, Bahia, based on the physical-chemical and microbiological parameters established by Ordinance MS No. 518/2004. Six water samples were collected from strategic points (drinking fountains, kitchens, and restrooms) at Horácio de Matos and Professor Roberto Santos Municipal Schools. Laboratory analyses were performed using the Alfakit kit at the Laboratory of the Pitágoras School of Medicine. Results showed that while Professor Roberto Santos School complied with all potability standards, Horácio de Matos School displayed nonconformities regarding pH and total coliforms. The study was conducted in accordance with ethical guidelines, with informed consent and formal authorization granted by school principals. As a pedagogical component, educational actions were carried out with the school community to promote awareness and encourage hygiene practices. The findings demonstrate that assessing water quality in schools is a crucial measure for sanitary surveillance and health promotion, particularly when combined with community-based educational strategies.